2021
DOI: 10.21608/ejhc.2021.196303
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress and Presenteeism Prevalence among Nursing Staff during the Outbreak of Pandemic Coronavirus Disease 2019

Abstract: Background: Job stress and presenteeism are perplexing issues in the nursing profession during the crisis of COVID-19 pandemic that must receive increasing attention. Aim: It aimed to assess the job stress and presenteeism prevalence, as well as verify the association between two concepts among nursing staff during the outbreak of coronavirus disease 2019. Design: It utilized a descriptive, correlational design. Setting: It was conducted in the Main Tanta University and Emergency Hospitals. Subjects: All nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Prevalence reached 98.2% in a study conducted on 503 Egyptian nurses. Participants attributed organizational factors such as fear of disciplinary action, staff shortages and limited pay for absenteeism and personal factors such as job insecurity, shortage of alternative job opportunities and professional obligation to the community as likely causes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence reached 98.2% in a study conducted on 503 Egyptian nurses. Participants attributed organizational factors such as fear of disciplinary action, staff shortages and limited pay for absenteeism and personal factors such as job insecurity, shortage of alternative job opportunities and professional obligation to the community as likely causes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results in agreement with the study conducted by Elsherbiny et al (2022) (24) who found that all studied nurses reported having sickness presenteeism associated with all physical health problem and disorders during the last 12 months especially in intensive care units. Furthermore, Mohamed et al (2021) (25) displayed that the vast majority of nurses experienced sickness presenteeism and more than half of them had two to five times frequency of occurrence. In this aspect, Mekonnen et al (2018) (26) claimed a high overall prevalence of sickness presenteeism among healthcare workers, accompanied by two to more than five times the frequency of occurrence.…”
Section: Data Collection Techniquementioning
confidence: 99%
“…n contrary, Shan et al (2020) (32) concluded that workload, leave system, and conscientiousness are the main causes for nurses sickness presenteeism, as well as financial demands as an important reason that was likely neglected by chief nurses. Mohamed et al (2021) (25) found out that organizational factors, including fear of disciplinary actions, the stuff shortage, organizational policy and limited baying for sick absence were the most dominant reasons for sickness presenteeism among nursing staff rather than personal factors such as job insecurity, lacking job opportunities, being appreciated as productive members, professional obligation and work commitment. Concerning perception of Stanford presenteeism dimensions, the current study revealed that the overall mean score of the completing work dimension was higher than the avoiding distraction dimension, in which around the two-thirds of nurses had a moderate overall score of scale items.…”
Section: Data Collection Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic continues to highlight the need to address healthcare staff’s occupational health, especially nurses, whose mental [ 20 , 21 ] and physical health [ 22 ] have been severely affected over the last 2 years [ 23 ]. Because of healthcare systems’ inability to meet all the care needs of every patient during epidemic episodes, presenteeism came under the spotlight [ 24 ].…”
Section: Introductionmentioning
confidence: 99%